Improvement in Anthropometric Measurements of Malnourished Children by Means of Complementary Food and Nutritional Education in Fars Province, Iran: A Community-Based Intervention - Shenavar, Razieh; Sajjadi, Seyedeh Forough; Farmani, Azam; Zarmehrparirouy, Mina; Azadbakht, Leila (Frontiers in Nutrition, 2022)
Background: Childhood malnutrition could have adverse impacts on the child's growth and eventually on fertility and general economic growth, and still, this issue remains a worldwide priority and a concern. This study aimed to evaluate the effectiveness of the national nutritional interventions program on the improvement and nutritional status of malnourished children under 60-month-old. Methods: This community-based intervention study was conducted with 1288 acute and moderate malnourished children between 6 and 56 months old referred to health centers. Children received combined nutritional education and counseling with the provision of affordable complementary food for ten months. Anthropometric measurements were assessed monthly according to the standard protocols. Results: Our results showed the reduction in the risk of malnutrition among children after nutritional interventions for weight-for-height (WHZ) (P<0.0001), height-for-age (HAZ) (P<0.0001), and weight-for-age (WAZ) (P=0.008). Controlling potential confounders such as socioeconomic status, childrens' birth supine length, and weight did not affect these findings and, malnourished children indicated improvement in HAZ index in <−2SD (OR=2.36, 95%CI=1.06-5.22, p=0.03) and <−3SD (OR=3.58, 95%CI=1.61-7.96, p=0.002) groups even after adjustment. Similarly, indices of malnourished status in WAZ <−2SD (OR=4.49, 95%CI=1.99-10.13, p=<0.001) and <−3SD (OR=5.94, 95%CI=2.63-13.41, p=<0.001) as well as WHZ <−2SD (OR=2.37, 95%CI=1.08-5.17, p=0.03) and <−3SD (OR=3.08, 95%CI=1.40 -6.74, p=0.005) showed the same pattern after the intervention period. Conclusion: Nutritional training and counseling as well as complementary food intervention among malnourished children significantly improved the nutritional status of children. So community-based intervention is recommended to reduce malnutrition among children.